(untitled) (Research, Society and Development, 2021)
Congenital heart diseases consist of structural defects of the heart and represent serious malformations, which manifest in newborns, contributing significantly to perinatal mortality. The dental management of patients with this condition may require caution by professionals, owing to the possibility of bleeding and the risk of causing an infectious endocarditis due to the variety of microorganisms residing in the oral cavity. The present case report aimed to detail dental care under general anesthesia in a hospital for a child with congenital heart disease. Female patient, 4 years old, was diagnosed with atrial and interventricular communication and hemodynamic repercussion 21 days after birth. The patient received dental treatment according to the proposed plan, which included dental restorations, conservative pulp therapy and extraction of lower anterior teeth. Posteriorly, a removable partial prosthesis was made for the patient for the purpose of functional aesthetic rehabilitation. The use of general anesthesia may reduce the risk of infective endocarditis and allows the performance of several dental procedures with a single antibiotic prophylaxis, since the cardiac pediatric patient needs a correct planning of the procedures to be performed.